FIFA Sudden Death Registry (FIFA-SDR): a prospective, observational study of sudden death in worldwide football from 2014 to 2018. Issue 2 (23rd December 2020) - Egger, Florian; Scharhag, Jürgen; Kästner, Andreas; Dvořák, Jiří; Bohm, Philipp; Meyer, Tim
Abstract : Objective: To investigate the underlying causes and regional patterns of sudden death in football (soccer) players worldwide to inform and improve existing screening and prevention measures. Methods: From 2014 to 2018 cases of sudden cardiac death (SCD), survived sudden cardiac arrest (SCA) and traumatic sudden death were recorded by media monitoring (Meltwater), a confidential web-based data platform and data synchronisation with existing national Sudden Death Registries (n=16). Inclusion criteria were met when sudden death occurred during football-specific activity or up to 1 hour afterwards. Death during other activities was excluded. Results: A total of 617 players (mean age 34±16 years, 96% men) with sudden death were reported from 67 countries; 142 players (23%) survived. A diagnosis by autopsy or definite medical reports was established in 211 cases (34%). The leading cause in players >35 years was coronary artery disease (76%) and in players ≤35 years was sudden unexplained death (SUD, 22%). In players ≤35 years the leading cause of SCD varied by region: cardiomyopathy in South America (42%), coronary artery anomaly in North America (33%) and SUD in Europe (26%). Traumatic sudden death including commotio cordis occurred infrequently (6%). Cardiopulmonary resuscitation (CPR) resulted in a survival rate of 85% with the use of an automated external defibrillator (AED) compared with 35% without. Conclusions: Regional variation in SCD aetiology should be verified by expansion of national registries and uniform autopsy protocols. Immediate access to an AED at training and competition sites, as well as CPR training for players, coaches and staff members, is needed to improve survival from SCA.